PENGENDALIAN PROSES STATISTIK UNTUK MENINGKATKAN PRODUKTIVITAS DAN KUALITAS PADA INDUSTRI - Endro Prihastono (Jurnal Ilmiah Dinamika Teknik, 2012)
Statistical Process Control (SPC) methods have been widely recognized as effective approaches for process monitoring and diagnosis. Statistical process control provides use of the statistical principals and techniques at every stage of the production. Statistical Process Control (SPC) aims to control quality characteristics on the methods, machine, products, equipments both for the company and operators with magnificent seven. Some simple techniques like the “seven basic quality control (QC) tools” provide a very valuable and cost effective way to meet these objectives. However, to make them successful as cost effective and problem solving tools, strong commitment from top management is required. Statistical process control (SPC) is one of the important tools in quality control (QC). In order to survive in a competitive market, improving quality and productivity of product or process is a must for any company. Keywords: Statistical Process Control (SPC) ; Statistical Quality Control (SQC); Quality Improvement; Quality Tools and Control Charts